MENJADI PEWARTA INJIL YANG IDEAL DI ERA KONSUMERISME: PERSPEKTIF TEKS MARKUS 6:7-13 - Juang, Afrianus (CREDENDUM: Jurnal Pendidikan Agama, 2020)
The purpose of writing this article is to make us aware as ideal disciples of Jesus amidst the onslaught of consumerism practices that permeate all aspects of human life. Becoming a disciple of Jesus is a calling that must be carried out totally and with full surrender. In today's era, to become a faithful disciple and be able to survive every challenge is very difficult. One of the trends that we are currently experiencing is the practice of consumerism that has seeped into the lower classes. Simultaneously, this culture of consumerism is contrary to the spirit of life as a disciple of Jesus that was passed down by Jesus directly to His disciples. Becoming a herald in this era is also very difficult because we are required to continue to live the lifestyle that was passed down directly by Jesus. In this article I want to present again the message of Jesus contained in the text Mark 6: 7-10, so that we become ideal heralds in the present and in the future.